An unusual case of gastrointestinal tract occlusion, Ladd's syndrome and neuroendocrine tumour of the appendix in a 19-year-old female patient - Misanik, M; Grajciar, M; Smolár, M; Miklusica, J; Cmarkova, K (Rozhledy v chirurgii, 2023)
Ladd's syndrome is a complex gastrointestinal anomaly that occurs based on congenital intestinal malrotation and leads to midgut volvulus and intestinal obstruction. It is mostly discovered in paediatric patients and presents itself in 90% of cases within the first year of life. It is a rare diagnosis in adult patients. We present the case report of a 19-year-old female patient with chronic abdominal pain and upper-type dyspeptic syndrome. MRI examination of the abdomen showed an abnormal location of the loops of the small intestine predominantly in the right part of the abdomen, caecum and c. ascendens in the epigastrium, duodenojejunal transition compressed and stenotized between upper mesenteric vessels and the aorta, with prestenotic dilatation of the duodenum and stomach and the "whirlpool sign" in mesentery. The patient was indicated for operational procedure and Ladd's operation was successfully performed laparoscopically, where "Ladd's bands" were divided; the procedure also included adhesiolysis, mobilization of the duodenum with its straightening, widening of the base of the mesentery, appendectomy and removal of an incidental solitary mesothelial cyst. A highly differentiated incidental neuroendocrine tumour of the apex of appendix was confirmed by histology. In the discussion, we focus on the rarity of intestinal malrotation in adulthood, clinical manifestation of the disease, diagnostic options and surgical treatment.
Keywords: nádory apendixu; Appendiceal Neoplasms; apendix; Humans; laparoskopie; střeva; neuroendokrinní nádory; Intestines; Female; mladý dospělý; Digestive System Abnormalities; Ladd’s band; bowel obstruction; lidé; Neuroendocrine Tumors; Appendix; ženské pohlaví; abnormality trávicího systému; Laparoscopy; Young Adult; volvulus intestini; gut malrotation; Intestinal Volvulus